Graphene composite material loaded with metal group clusters as well as preparation method and application of graphene composite material
By introducing ionic liquid into graphene materials, combined with magnetron sputtering method and time-flight quality selection technology, the composite material preparation of graphene and metal clusters is achieved, solving the problems of incomplete cluster structure and unstable performance in traditional methods, and a composite material with wide application prospects is obtained.
Patent Information
- Application Number
- CN202411724051.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional magnetron sputtering method is difficult to directly realize the preparation of composite materials between graphene and metal clusters, resulting in wide distribution of cluster atoms and incomplete structure, making it difficult to prepare macroscopically and stabilize performance.
Ion liquid containing graphene material is used to collect metal clusters synthesized by the magnetron sputtering method, and the number of cluster atoms is regulated by the time flight mass selection, and the cluster structure is protected by the ionic liquid to achieve solid loading between clusters and graphene.
A fully structurally complete, stable physical properties and macro-preparable metal clusters/metal oxide clusters/graphene composite material have been obtained, which has expanded its application prospects in the fields of antibacterial, catalysts and electrochemical sensing materials.
Smart Images

Figure CN119506810A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a graphene composite material loaded with metal group clusters, and a preparation method and application thereof. Background Art
[0002] Clusters are relatively stable microscopic aggregates composed of several or even tens of thousands of atoms. They are new substances between the sizes of atoms, molecules and condensed matter. Their structure and physical and chemical properties are not only different from atoms and blocks, but also change dramatically with the change of their own atomic number. Metal cluster materials have excellent biocompatibility and efficient catalysis, and can be used to prepare different functional materials. Magnetron sputtering gas phase synthesis is a commonly used method for preparing metal clusters. It can directly control the beam and mass selection through electric fields to produce atomic clusters with a size of 2 to at least 70,000 atoms. However, the conventional direct use of solid substrates such as carbon films or silicon wafers to collect clusters is prone to cause a wide distribution of cluster atoms and incomplete structures.
[0003] Graphene and its derivatives have been widely used in materials, information, electronics, information, energy and other fields due to their ultra-high specific surface area and excellent electrical and thermal conductivity. Their unique two-dimensional sheet structure and surface active groups have also been widely studied because of their unique role in the antibacterial field.
[0004] Based on the characteristics of graphene materials and metal clusters, combining the two to form composite materials is the focus of current research. However, traditional magnetron sputtering cannot directly achieve the preparation of graphene-metal cluster composite materials. Therefore, how to prepare composite materials containing graphene and metal clusters with complete structure, stable performance and large quantity is an urgent problem to be solved in this field. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a graphene composite material loaded with metal clusters, and a preparation method and application thereof. The present invention collects metal clusters synthesized in the gas phase by magnetron sputtering by using an ionic liquid containing graphene materials, and realizes clusters with adjustable atomic number by magnetron sputtering time-of-flight mass selection; at the same time, the integrity of the cluster structure and solid collection are realized by the ionic liquid and the graphene material contained therein, giving full play to the synergistic effect of the three, and obtaining a loaded metal cluster / metal oxide cluster / graphene composite material with complete structure, stable physical properties, and large-scale preparation.
[0006] The technical solution of the present invention is as follows: The first aspect of the present invention provides a method for preparing a graphene composite material loaded with metal group clusters, the preparation method comprising the following steps: S1: Adding graphene material into ionic liquid and dispersing to obtain cluster collection liquid.
[0007] S2: Load the cluster collection liquid into the cluster collection dish, use magnetron sputtering to synthesize the metal cluster beam from the metal target in the gas phase, and then use the time-of-flight mass selection method to allow cluster beams with different atomic numbers to enter the cluster collection dish to obtain a graphene composite material dispersion loaded with metal group clusters.
[0008] S3: Solid-liquid separation, the obtained solid is the graphene composite material loaded with metal group clusters.
[0009] Preferably, in step S1, the graphene material refers to a graphene material with an oxygen content ≥ 10%.
[0010] Preferably, the graphene material is at least one of graphene oxide and redox graphene.
[0011] Preferably, in step S1, the ionic liquid refers to a room temperature ionic liquid, and the ionic liquid includes at least one cation selected from the group consisting of quaternary ammonium salt ions, quaternary phosphonium salt ions, imidazolium salt ions, and pyrrole salt ions, preferably at least one cation selected from the group consisting of imidazolium salt cations and pyrrole salt cations.
[0012] Preferably, in step S1, the concentration of the graphene material in the cluster collection solution is 0.01-10 mg / mL.
[0013] Preferably, in step S2, the purity of the metal target material is 99.9-99.999%, and the metal target material includes one or more of Zn, Ti, W, Fe, and Sn.
[0014] Preferably, in step S2, the time-of-flight mass selection method refers to applying longitudinal electric fields with different pulse widths when the metal cluster beam prepared by magnetron sputtering flies horizontally, so that metal group clusters with different atomic numbers are drawn out and collected at the outlet, thereby realizing the regulation of the atomic number of the metal clusters; when the atomic number of the loaded metal group clusters is ≤2000±100, the metal group clusters are metal oxide clusters; when the atomic number of the loaded metal group clusters is >2000±100, the metal group clusters are metal oxide-coated metal clusters.
[0015] Preferably, in step S3, after the solid-liquid separation, the process of oxidizing the obtained solid is also included, and the temperature of the oxidation treatment is 180-250° C. and the time is 30-120 min.
[0016] The second aspect of the present invention provides a graphene composite material loaded with metal group clusters prepared by the preparation method described in the first aspect, wherein the loading amount of the metal group clusters in the graphene composite material is 0.01-60wt%.
[0017] The third aspect of the present invention provides an application of a graphene composite material loaded with metal group clusters prepared by the preparation method described in the first aspect or the graphene composite material loaded with metal group clusters described in the second aspect, wherein the graphene composite material loaded with metal group clusters is used for the preparation of antibacterial materials, catalyst materials, and electrochemical sensor materials.
[0018] The beneficial technical effects of the present invention are: The present invention improves the diffusivity of the metal target material by introducing ionic liquid, thereby realizing the protection of the integrity of the cluster structure; at the same time, the presence of the graphene material in the ionic liquid realizes the fixation of the metal group clusters on the graphene material under its unique two-dimensional structural characteristics; in addition, the cluster atomic number is regulated by selectively regulating the cluster beam through magnetron sputtering time flight mass.
[0019] The present invention further controls the parameters of graphene. The oxygen content of the graphene material used is not less than 10%. A large number of oxygen-containing functional groups exist on the surface of the graphene material. While achieving metal cluster loading, the metal clusters are further converted into corresponding metal oxide clusters, thereby expanding its application.
[0020] The clusters prepared by the preparation method of the present invention have a complete structure, can realize customized preparation of cluster atoms and diversified preparation of metal clusters and metal oxide clusters, and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a TEM characterization image of the Ag cluster-loaded graphene composite material prepared in Example 1 of the present invention.
[0022] Figure 2 This is a diagram showing the antibacterial effect of the ZnO cluster-loaded graphene composite material prepared in Example 1 of the present invention on Streptococcus mutans at different concentrations.
[0023] Figure 3 This is a TEM characterization image of the graphene composite material loaded with TiO2@Ti clusters prepared in Example 2 of the present invention.
[0024] Figure 4 The antibacterial effect of the graphene composite material loaded with TiO2@Ti clusters prepared in Example 2 of the present invention on Streptococcus mutans at different concentrations.
[0025] Figure 5 This is a TEM characterization image of the graphene composite material loaded with WO3@W clusters prepared in Example 3 of the present invention.
[0026] Figure 6 The antibacterial effect of the graphene composite material loaded with WO3@W clusters prepared in Example 3 of the present invention on Streptococcus mutans at different concentrations.
[0027] Figure 7 This is a TEM characterization image of the graphene composite material loaded with Fe2O3 clusters prepared in Example 4 of the present invention.
[0028] Figure 8 The antibacterial effect of the graphene composite material loaded with Fe2O3 clusters prepared in Example 4 of the present invention on Streptococcus mutans at different concentrations.
[0029] Fig. 9 It is a schematic diagram of the equipment system used for magnetron sputtering with time-of-flight mass selection mode of the present invention. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0031] The first aspect of the present invention provides a method for preparing a graphene composite material loaded with metal group clusters, the preparation method comprising the following steps: S1: Adding graphene material into ionic liquid and dispersing to obtain cluster collection liquid.
[0032] S2: Load the cluster collection liquid into the cluster collection dish, use magnetron sputtering to synthesize the metal cluster beam from the metal target in the gas phase, and then use the time-of-flight mass selection method to allow cluster beams with different atomic numbers to enter the cluster collection dish to obtain a graphene composite material dispersion loaded with metal group clusters.
[0033] S3: Solid-liquid separation, the obtained solid is the graphene composite material loaded with metal group clusters.
[0034] The present invention improves the diffusivity of the metal target material by introducing ionic liquid, thereby realizing the protection of the integrity of the cluster structure; at the same time, the presence of the graphene material in the ionic liquid realizes the fixation of the metal group clusters on the graphene material under its unique two-dimensional structural characteristics; in addition, the cluster atomic number is regulated by selectively regulating the cluster beam through magnetron sputtering time flight mass.
[0035] The clusters prepared by the preparation method of the present invention have a complete structure, can realize customized preparation of cluster atoms and diversified preparation of metal clusters and metal oxide clusters, and have broad application prospects.
[0036] In some embodiments, in step S1, the graphene material refers to a graphene material with an oxygen content ≥ 10%.
[0037] In some embodiments, the graphene material is at least one of graphene oxide with an oxygen content of ≥10% and redox graphene with an oxygen content of ≥10%.
[0038] The present invention controls the parameters of graphene. When the oxygen content of the graphene material used is not less than 10%, a large number of oxygen-containing functional groups exist on its surface. These functional groups act as "anchor points" to chemically react with clusters, firmly fix and immobilize metal group clusters on the graphene surface. Therefore, while realizing the metal cluster loading, the metal clusters can be further converted into corresponding metal oxide clusters, thereby expanding its application. If the oxygen content is too low, these reactive "anchor points" will become less, and the immobilization amount of the final product metal group cluster will be less, or the immobilization is not tight enough and is easy to fall off, thereby affecting the stability of later applications.
[0039] In some embodiments, in step S1, the ionic liquid refers to a room temperature ionic liquid, including at least one cation selected from the group consisting of quaternary ammonium salt ions, quaternary phosphonium salt ions, imidazolium salt ions, and pyrrole salt ions. Preferably, the ionic liquid is an ionic liquid of imidazolium salt cations and pyrrole salt cations that can undergo π-π interactions with graphene materials.
[0040] It is understandable that the ionic liquid includes at least one of quaternary ammonium salt ionic liquids, quaternary phosphonium salt ionic liquids, imidazole ionic liquids, and pyrrole ionic liquids.
[0041] In some embodiments, in step S1, the concentration of the graphene material in the collected liquid is 0.01~10 mg / mL, including but not limited to 0.01 mg / mL, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL, and 10 mg / mL.
[0042] In some embodiments, in step S2, the purity of the metal target material is 99.9%-99.999%, and the metal target material includes one or more of Zn, Ti, W, Fe, and Sn.
[0043] In some embodiments, in step S2, the parameters of the magnetron sputtering gas phase synthesis technology are: sputtering power 40-100W, sputtering gas is Ar gas, Ar gas flow rate is 100-180sccm, condensing gas is He gas, condensing gas pressure is 17-30pa, condensing distance is 12-30cm; pulse voltage is 0.5-1kv.
[0044] In some embodiments, in step S2, the time-of-flight mass selection method refers to applying longitudinal electric fields with different pulse widths when the metal cluster beam prepared by magnetron sputtering flies horizontally, so that clusters with different atomic numbers are drawn out and collected at the exit, thereby realizing the regulation of the atomic number of the metal clusters.
[0045] The present invention does not limit the equipment used in step S2. Any equipment that can achieve the purpose of the present invention is within the protection scope of the present invention. Exemplarily, step S2 can be achieved by combining a magnetron sputtering device with a time-of-flight mass selection system. Fig. 9 The schematic diagram of the device system used for magnetron sputtering with time-of-flight mass selection of the present invention. As can be seen from the figure, the metal target material synthesizes the metal cluster beam in the magnetron sputtering cluster preparation system through the gas phase. When the metal cluster beam flies horizontally, the longitudinal electric field with different pulse widths is applied to make the metal group clusters with different atomic numbers be collected at the outlet, so as to achieve the regulation of the atomic number of the metal cluster.
[0046] In some embodiments, when the number of atoms of the loaded metal cluster is ≤2000±100, the metal cluster reacts with the oxygen-containing functional groups on the surface of the graphene derivative to transform into corresponding metal oxides, such as TiO2, ZnO, WO3, Fe2O3, SnO2, etc.
[0047] In some embodiments, when the number of atoms of the loaded metal group clusters is greater than 2000±100, some of the metal clusters react with the oxygen-containing functional groups on the surface of the graphene material to transform into corresponding metal oxide-coated metal clusters, such as TiO2@Ti, ZnO@Zn, WO3@W, Fe2O3@Fe, SnO2@Sn, forming a coating structure of metal oxide clusters and metal clusters.
[0048] In some embodiments, in step S3, after solid-liquid separation, the solid obtained is further subjected to an oxidation treatment process, wherein the metal-containing clusters are completely converted into metal oxides by oxidation reaction, and the oxidation treatment temperature is 180-250°C and the time is 30-120 minutes. That is to say, when the number of atoms of the metal group clusters supported by graphene is greater than 2000±100, only part of the metal clusters react with the oxygen-containing functional groups on the surface of the graphene derivative to be converted into corresponding metal oxides. If antibacterial properties are to be achieved, the metal can be further oxidized into metal oxides to improve antibacterial properties.
[0049] A second aspect of the present invention provides a graphene composite material loaded with metal group clusters prepared by the preparation method described in the first aspect, wherein the loading amount of the metal group clusters in the graphene composite material is 0.01-60wt%, including but not limited to 0.01wt%, 0.05wt%, 1wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, and 60wt%.
[0050] The third aspect of the present invention provides an application of a graphene composite material loaded with metal group clusters prepared by the preparation method described in the first aspect or the graphene composite material loaded with metal group clusters described in the second aspect, wherein the graphene composite material loaded with metal group clusters is used for the preparation of antibacterial materials, catalyst materials, and electrochemical sensor materials.
[0051] The following are specific embodiments.
[0052] Example 1 A graphene composite material loaded with metal group clusters, wherein the preparation method thereof comprises the following steps: (1) Ultrasonic dispersion of 5 g of graphene oxide (oxygen content 25%) into 500 mL of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt [C2MIM]NTf2 ionic liquid was performed to prepare an ionic liquid with a graphene oxide concentration of 10 mg / mL. 50 mL of the liquid was taken as the cluster collection liquid and loaded into the cluster collector. (2) Zn with a purity of 99.9% was selected as the target material, and the magnetron sputtering gas phase synthesis technology was adopted. The sputtering power was set to 60 W, the sputtering gas was Ar gas, the Ar gas flow rate was 180 sccm, the condensing gas was He gas, the condensing gas pressure was 17 Pa, and the condensing distance was 12 cm. The magnetron sputtering gas phase synthesis equipment system (including the time mass selection system) was used to prepare Zn clusters with an atomic number of 500±10, where the pulse voltage was 0.6 kV.
[0053] (3) By centrifugal separation, a graphene composite material loaded with ZnO clusters was obtained. The loading amount of metal group clusters in the graphene composite material was 1 wt%. The TEM characterization image is shown in Figure 1 .
[0054] The obtained graphene composite material loaded with ZnO clusters was prepared by adding water to obtain four different concentrations of 20 μg / mL, 10 μg / mL, 5 μg / mL, and 1 μg / mL, and then incubated with Streptococcus mutans for 10 min. 5 The antibacterial effect was tested by contacting for 12 hours. Figure 2 As shown in the figure, each concentration showed obvious antibacterial effect.
[0055] Example 2 A graphene composite material loaded with metal group clusters, wherein the preparation method thereof comprises the following steps: (1) Ultrasonic dispersion of 0.5 g of graphene oxide (oxygen content 40%) into 500 mL of 1-butyl-1-methylpyrrolidine bis(trifluoromethylsulfonyl)imide ([BMPyrr][Tf2N]) ionic liquid was performed to prepare an ionic liquid with a graphene oxide concentration of 1 mg / mL. 50 mL of the liquid was taken as the cluster collection liquid and loaded into the cluster collector. (2) Ti with a purity of 99.99% was selected as a suitable target material, and magnetron sputtering gas phase synthesis technology was adopted. The sputtering power was set to 80 W, the sputtering gas was Ar gas, the Ar gas flow rate was 180 sccm, the condensing gas was He gas, the condensing gas pressure was 20 Pa, and the condensing distance was 12 cm. The magnetron sputtering gas phase synthesis equipment system (including the time mass selection system) was used to prepare Ti clusters with an atomic number of 2000±100, where the pulse voltage was 0.5 kV.
[0056] (3) A graphene composite material loaded with titanium oxide-coated titanium (TiO2@Ti) clusters was obtained by centrifugal separation. The loading amount of metal group clusters in the graphene composite material was 25wt%. The TEM characterization image is shown in Figure 3 .
[0057] The obtained graphene composite material loaded with TiO2@Ti clusters was prepared by adding water to obtain four different concentrations of 20 μg / mL, 10 μg / mL, 5 μg / mL, and 1 μg / mL, respectively, and then incubated with Streptococcus mutans for 10 min. 5 The antibacterial effect was tested by contacting for 12 hours. Figure 4 As shown in the figure, each concentration showed obvious antibacterial effect.
[0058] Example 3 A graphene composite material loaded with metal group clusters, wherein the preparation method thereof comprises the following steps: (1) Ultrasonic dispersion of 0.1 g of redox graphene (oxygen content 15%) into 500 mL of N,N,N-tributyl-N-octylaminemethanesulfonate ammonium ionic liquid was performed to prepare an ionic liquid with a redox graphene concentration of 0.2 mg / mL. 50 mL of the liquid was taken as the cluster collection liquid and loaded into the cluster collector.
[0059] (2) W with a purity of 99.9% was selected as the target material, and the magnetron sputtering gas phase synthesis technology was used. The sputtering power was set to 40 W, the sputtering gas was Ar gas, the Ar gas flow rate was 120 sccm, the condensing gas was He gas, the condensing gas pressure was 30 Pa, and the condensing distance was 20 cm. The magnetron sputtering gas phase synthesis technology (including the time mass selection system) was used to prepare W clusters with an atomic number of 3000±100, where the pulse voltage was 0.6 kV.
[0060] (3) The graphene oxide composite material loaded with WO3@W clusters was obtained by centrifugal separation. The loading amount of metal group clusters in the graphene composite material was 40wt%. The TEM characterization image is shown in Figure 5 .
[0061] The obtained graphene composite material loaded with WO3@W clusters was prepared by adding water to obtain four different concentrations of 20 μg / mL, 10 μg / mL, 5 μg / mL, and 1 μg / mL, respectively, and then incubated with Streptococcus mutans for 10 5 The antibacterial effect was tested by contacting for 12 hours. Figure 6 As shown in the figure, it can be seen that each concentration shows good antibacterial effect.
[0062] Example 4 A graphene composite material loaded with metal group clusters, wherein the preparation method thereof comprises the following steps: (1) Ultrasonic dispersion of 0.05 g of redox graphene (oxygen content 50%) into 500 mL of 1-dodecyl imidazolium trifluoromethanesulfonate ionic liquid was performed to prepare an ionic liquid with a redox graphene concentration of 0.1 mg / mL. 50 mL of the liquid was taken as cluster collection liquid and loaded into a cluster collector.
[0063] (2) Fe with a purity of 99.9% was selected as a suitable target material, and a magnetron sputtering gas phase synthesis technology was used. The sputtering power was set to 100 W, the sputtering gas was Ar gas, the Ar gas flow rate was 100 sccm, the condensing gas was He gas, the condensing gas pressure was 20 Pa, and the condensing distance was 30 cm. The magnetron sputtering gas phase synthesis technology (including the time mass selection system) was used to prepare Fe clusters with an atomic number of 7000±500, where the pulse voltage was 0.6 kV.
[0064] (3) The redox graphene composite material loaded with Fe2O3@Fe clusters was obtained by centrifugal separation.
[0065] (4) The obtained redox graphene composite material loaded with Fe2O3@Fe clusters was placed in a tube furnace and heat treated at 200°C for 1 h in an air atmosphere. The Fe clusters were oxidized to Fe2O3 with the help of oxygen in the air, and finally a graphene composite material loaded with Fe2O3 was obtained. The loading amount of metal group clusters in the graphene composite material was 40wt%. The TEM characterization image is shown in Figure 7 .
[0066] The obtained graphene composite material loaded with Fe2O3 clusters was prepared by adding water to obtain four different concentrations of 20 μg / mL, 10 μg / mL, 5 μg / mL, and 1 μg / mL, respectively, and then incubated with Streptococcus mutans for 10 min. 5 The antibacterial effect was tested by contacting for 12 hours. Figure 8 As shown in the figure, it can be seen that each concentration shows good antibacterial effect.
[0067] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.
Claims
1. A method for preparing a graphene composite material loaded with metal group clusters, characterized in that: The preparation method comprises the following steps: S1: adding graphene material into ionic liquid and dispersing to obtain cluster collection liquid; S2: Loading the cluster collection liquid into a cluster collection dish, synthesizing a metal cluster beam from a metal target in the gas phase by magnetron sputtering, and then using a time-of-flight mass selection method to allow cluster beams with different atomic numbers to enter the cluster collection dish to obtain a graphene composite material dispersion loaded with metal group clusters; S3: Solid-liquid separation, the obtained solid is the graphene composite material loaded with metal group clusters.
2. The preparation method according to claim 1, characterized in that: In step S1, the graphene material refers to a graphene material with an oxygen content ≥ 10%.
3. The preparation method according to claim 2, characterized in that: The graphene material is at least one of graphene oxide and redox graphene.
4. The preparation method according to claim 1, characterized in that: In step S1, the ionic liquid refers to a room temperature ionic liquid, and the ionic liquid includes at least one cation selected from the group consisting of quaternary ammonium salt ions, quaternary phosphonium salt ions, imidazolium salt ions, and pyrrole salt ions, preferably at least one cation selected from the group consisting of imidazolium salt cations and pyrrole salt cations.
5. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the graphene material in the cluster collection solution is 0.01-10 mg / mL.
6. The preparation method according to claim 1, characterized in that: In step S2, the purity of the metal target material is 99.9-99.999%, and the metal target material includes one or more of Zn, Ti, W, Fe, and Sn.
7. The preparation method according to claim 1, characterized in that: In step S2, the time-of-flight mass selection method refers to applying longitudinal electric fields with different pulse widths when the metal cluster beam prepared by magnetron sputtering is flying horizontally, so that metal clusters with different atomic numbers are drawn out and collected at the outlet, thereby realizing the regulation of the atomic number of the metal clusters; When the number of atoms of the supported metal group cluster is ≤2000±100, the metal group cluster is a metal oxide cluster; When the number of atoms of the supported metal group cluster is greater than 2000±100, the metal group cluster is a metal oxide-coated metal cluster.
8. The preparation method according to claim 1, characterized in that: In step S3, after the solid-liquid separation, the obtained solid is further subjected to an oxidation treatment process, wherein the oxidation treatment temperature is 180-250° C. and the time is 30-120 min.
9. A graphene composite material loaded with metal group clusters prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The loading amount of the metal group cluster in the graphene composite material is 0.01-60wt%.
10. Use of a graphene composite material loaded with metal group clusters prepared by the preparation method according to any one of claims 1 to 8 or a graphene composite material loaded with metal group clusters according to claim 9, characterized in that: The graphene composite material loaded with metal group clusters is used for the preparation of antibacterial materials, catalyst materials and electrochemical sensor materials.